Socially optimal sustainability standards with non-consequentialist ("warm glow") investors - Roman Inderst; Markus Opp (Leibniz Institute for Financial Research SAFE, 2022)
Agencies around the world are in the process of developing taxonomies and standards for sustainable (or ESG) investment products. A key assumption in our model is that of non-consequentialist private investors (households) who derive a "warm glow" decisional utility when purchasing an investment product that is labelled as sustainable. We ask when such labelling is socially beneÖcial even when the social planner can impose a minimum standard on investment and production. In a model of Önancial constraints (Holmström and Tirole 1997), which we close to include consumer surplus, we also determine the optimal labelling threshold and show how its stringency is aected by determinants such as the prevalence of warm-glow investor preferences, the presence of social network eects, or the relevance of Önancial constraints at the industry level.
Keywords: 330; Sustainability; ESG; green financing; labelling